[PP.21.12] GENDER-DIFFERENCES IN PREVALENCE OF KNOWN AND UNKNOWN HYPERTENSION AND THE RELATION TO VASCULAR AGE. (September 2017) - Hametner, B.; Mayer, C.; Parragh, S.; Whitelegg, K.; Weber, T.; Wassertheurer, S.
Abstract : Objective: Age-dependent differences between men and women are known for blood pressure levels as well as for parameters of arterial stiffness. Furthermore, many people are not aware of their cardiovascular risk or are not treated effectively. To raise awareness, the concept of vascular age has been developed, which translates elevated levels of arterial stiffness to aging. The aim of this study was to investigate gender-differences on blood pressure levels and the potential of vascular age as an additional tool to promote blood pressure control. Design and method: Blood pressure and pulse wave analysis measurements were performed in pharmacies in the city of Wels, Austria. Prior to the measurement, the subjects were asked if they were diagnosed with hypertension before and if they take antihypertensive drugs. Blood pressure levels were categorized according to the ESH/ESC guidelines in three groups per sex: optimal pressure, normal / high normal pressure and hypertension. Additionally, pulse wave velocity (PWV) and the difference between vascular and actual age of the subjects was calculated. Results: 441 (32%) measurements of men and 958 (68%) of women were recorded. 44% of males and 34% of females reported diagnosed hypertension. Of those with diagnosed hypertension, in both sexes 80% reported to take antihypertensive drugs. Nevertheless, more than half of subjects with diagnosed hypertension still had blood pressure values in the hypertensive range, and no statistical significance between sexes could be found (p = 0.15). In contrast, in subjects who did not report diagnosed hypertension, 46% of males but only 26% of females have been categorized as hypertensives (p < 0.0001). As can be seen in the table, the elevation of vascular age corresponds with blood pressure categories. Conclusions: In this study, the prevalence of hypertension was generally high. While no sex differences could be found in subjects with previously diagnosed hypertension, the percentage of subjects with unknown hypertension was higher in men. This describes the need for additional efforts for blood pressure control especially in men. Vascular age as an intuitive marker of age-dependent elevated arterial stiffness beyond absolute PWV values can potentially be used to raise awareness. Figure. No caption available.